Docosahexaenoic acid (DHA) injection in spinal cord transection stimulates Na+,K+-ATPase in skeletal muscle via Î² 1 subunit - Maixent, J. M.; Fares, M.; François, C.; Delmotte, A.; Rigoard, P. (Cellular and Molecular Biology, 2014)
Spinal cord injuries (SCI) induce a loss of skeletal muscle mass and functional capacity. The muscle excitability and contractility depend on the plasma membrane potential, regulated by transmembrane ion gradients, and thus necessarily on the Na+,K+-ATPase activity. The aim of this work was to evaluate the consequences of a spinal cord transection (SCT) on the skeletal muscle Na+,K+-ATPase and the impact of collateral GlyceroPhosphoLipids enriched in DocosaHexaenoic Acid (GPL-DHA) administration. The Na+,K+-ATPase activity and membrane expression of Na+,K+-ATPase Î±1, Î±2 and Î²1 isoforms were assessed by K+-stimulated paranitrophenyl phosphatase (pNPPase) measurements and Western Blotting, respectively. The results show that spinal cord transection increased significantly (p<0.05) Na+,K+-ATPase activity in muscle by 25% and decreased the amounts of Î±1 isoform and Î±2 isoform expressions by 50% (p<0.05) respectively compared to controls. The results also show that early injection of GPL-DHA after SCT decreases in membrane skeletal muscle the Î±1 and Î±2 isoforms expression but increases the membrane Na+,K+-ATPase activity. This treament partially restores the membrane expression of the Î²1 subunit of the Na+,K+-ATPase. These data suggest that the increase of Î²1 subunit expression is probably the main trigger to the membrane Na+,K+-ATPase activation following a trans-synaptic denervation.